Escopo de prática de médicos em atenção primária em saúde no Brasil - Ana Cristina de Sousa van Stralen (2021)
The scope of practice of Primary Health Care (PHC) professionals and its determinants has been the subject of studies in several countries that seeks innovative ways to respond to scenarios of shortage and poor distribution of professionals, especially physicians. Recently, the scope of practice has also entered the agenda of Health Human Resource (HRH) planners in Brazil. However, the number of studies on this topic in the country is still low. The present thesis aims to investigate the scope of practice of PHC physicians in Brazil and its main determinants. In addition, carry out a literature review on strategies of reducing barriers of health professionals' scope of practice regulations that have been recommended and/or implemented internationally, considering the current scenario of the COVID-19 pandemic. We developed three studies within this thesis. In Study 1, we analyzed data from an exploratory cross-sectional study, through an online survey, with 2.277 PHC physicians to identify differences in primary care physicians' scope of practice and to raise the main factors associated with expanded practice in rural and urban areas of Brazil. Differences regarding activities and procedures performed by physicians per location were verified by Kruskal-Wallis/Dunn's Post Hoc and Chi-square tests. Multivariate linear regression analyses were done using the bootstrap technique to identify the main factors associated with an expanded scope of practice. Study 2 aimed to define the profile of physicians in Brazil, considering their scope of practice and its determinants; we used data of a cross-sectional study, with 830 physicians of different levels of care. We used the method Grade of Membership (GoM). Four physicians’ profiles were gendered, considering medical specialty, the scope of practice, and the following determinants: i: personal factors, ii. education, and iii practice location. In Study 3 we carried out a scoping review to identify the main international strategies to reduce practice barriers of health professionals’ regulations that have been recommended and/or implemented in the context of the COVID-19 pandemic. In Study 1 regardless of the location, the results showed that primary care physicians are practicing below their competencies. Rural physicians performed a higher number of procedures and activities compared with their peers from intermediate and urban municipalities. Within the overall sample, the variables related to a broader scope of practice included: male gender, working in rural municipalities, participating in training and continuing education programs, and consulting clinical protocols, articles, and books. In Study 2 the results suggest that the scope of practice can be analyzed through four physicians’ profiles. Profile 1 and 2 were more likely to have a broader scope of practice and showed similarities concerning working o PHC facilities and specialties, in areas described as rural, unsafe/violent, and urban with a shortage of physicians. Physicians of profiles 3 and 4 have a less comprehensive scope of practice, especially those in profile 4. Both groups are Brazilian physicians who have the Qualification of Specialty Registration and are more likely to work in urban areas without physician shortage. In Study 3 the scoping review included 36 documents. The following strategies were identified: 1) enhancing health professionals’ scope of practice; 2) task-shifting from one professional category to another; 3) authorization and billing of telemedicine; 4) licensing and recruitment of non-active professionals; 5) changes in education and provision of targeted training. The three studies show that there are important variants in professionals’ practice, which must be analyzed in more depth. The recognition of these differences can be relevant to determine the competencies, training, and recourses required for physicians practicing in different locations, seeking to improve the quality and access of health care services. Study 3 reveals that many countries are experimenting with new ways to enhance their health workforce during the pandemic. Perhaps one of the most important strategies in response to scenarios of professional’s shortage and quickly meeting the needs of the population, has been the flexibility and willingness to adapt, expand and redistribute activities of health professionals. The review highlights the importance of carrying out reforms in the professional scope of practice regulations, to optimize the available health workforce, to quickly meet the health needs of the population.